For some reason, I'm having trouble understanding how this is done...
-(y-1)^2 = y-1
-(y-1) - (y-1)^2 = 0
-(y-1)(1+y-1) = 0
(1-y)y = 0
y=0, x=-1 or y=1, x=0
Could someone explain to me how that is possible?
-(y-1)^2 = y-1 ..................we begin here
-(y-1) - (y-1)^2 = 0 ..........we subtract (y - 1) from both sides
-(y-1)(1+y-1) = 0 .............we factor out the common -(y - 1)
(1-y)y = 0 ........................we simplify
now since (1 -y) and y multiplied gives zero, one or the other must be zero
so 1 - y = 0 or y = 0
=> y = 1, y = 0
got it?